OPTIMIZING TEAM ASSISTED INDIVIDUALIZATION TO IMPROVE STUDENTS’ WRITING SKILL - Sulaiman, Sulaiman (LPPM IKIP PGRI Pontianak, 2016)
This research is aimed to find out how the use of Team AssistedIndividualization (TAI) Instruction can improve students’ writing ability of personal recount text to the tenth grade students of SMA Santun Pontianakin the academic year of 2015/2016. The method of the research was conducted using Classroom Action Research (CAR). Then, there were totaled 22 students of the tenth grade students (XD) of SMA Santun Pontianak as the samples of research. The tools of collecting data were observation checklist, field note, and written test. TAI Instruction in teaching recount text was received well by the tenth grade students of SMA Santun Pontianak in the academic year of 2015/2016. TAI was very helpful in giving equal opportunity in learning. Implementing TAI Instruction could encourage and help one another because they wanted their team won. Based on the data, it was found that TAI instruction improved students’ behavior during CAR. They became more confident in writing a recount paragraph. Thus, it can be concluded that Team Assisted Individualization (TAI) Instruction improved students’ ability in writing personal recount text to the tenth grade students of SMA Santun Pontianak in the academic year of 2015/2016. TAI instruction is considered one of alternative teaching instruction that can be implemented in teaching writing.TAI Instruction would be helpful to enhance students’ writing ability and involve students actively in teaching and learning activity. So it is suggested that TAI instruction can be used as one of the alternative way in learning writing in the classroom. Keywords: Team Assisted Individualization (TAI), Writing, student’s writing skill, Classroom Action Research (CAR).